Assist-as-needed control based on region attractor for power-assist of knee joint taking into account differences in human and orthotic motion - Ken MASUYA; Yuta IDE; Masafumi OKADA (Nihon Kikai Gakkai ronbunshu)
This paper proposes an assist-as-needed (AAN) controller for power-assist of a knee joint that takes into account differences in human and orthotic motion. The AAN control is one control method that adjusts the assist performance according to the wearer’s ability. AAN controllers are often designed to be time-independent so that the wearer can act whenever he/she wants. However, the speed of human motion changes frequently, nevertheless, most previous works did not actively change the desired speed of the orthotic motion. This paper tackles this issue, and we propose a region attractor that changes the speed of the reference motion based on the internal force acting on the lower limb attachment point. In addition, to reduce pain at the attachment point caused by a misalignment between the wearer and the orthosis, the center of rotation (CoR) of the knee is estimated in real-time. Using the estimated CoR, the motor torque that satisfies the desired knee torque is generated while minimizing the internal force in the direction that does not contribute to assist. Through experiments using a dummy robot of the human knee with various torque limits, the effectiveness of the proposed method was verified.